Common cold among pre-school children in China - associations with ambient PM10 and dampness, mould, cats, dogs, rats and cockroaches in the home environment. (June 2017) - Norbäck, Dan; Lu, Chan; Zhang, Yinping; Li, Baizhan; Zhao, Zhuohui; Huang, Chen; Zhang, Xin; Qian, Hua; Sundell, Jan; Deng, Qihong
Abstract: Background: There is some evidence that dampness, mould and cockroaches can increase the risk of respiratory infections in children but few studies exist from China on this topic. Aim To study associations between domestic early life exposure to biological indoor factors (dampness, mould, cats, dogs, rats, cockroaches), cleaning habits and common cold among pre-school children across China. Methods: Children aged 3–6 years (n = 39, 782) were recruited from randomly selected day care centres in seven cities in China. Data on common cold and prenatal and postnatal exposure to dampness, mould, windowpane condensation in wintertime (WPC), cats, dogs, cockroaches and rats were assessed by a parentally administered questionnaire. Data on annual ambient temperature and PM10 was assessed on city level. Associations between high frequency (> 5 colds per year) and long duration (≥ 2 weeks) of common colds in the past year and exposure were calculated by multilevel logistic regression. Results: A total of 9.2% had a high frequency and 11.9% had long duration of common cold. Exposure to mould (OR = 1.38, 95% CI 1.24–1.53) and WPC (OR 1.23, 95%CI 1.13–1.33) at birth was associated with frequent common cold. Exposure to dogs at birth was associated with long duration of common cold. (OR = 1.22, 95% CI 1.06–1.41). Exposure to mould (OR = 1.36, 95% CI 1.22–1.54), WPC (OR = 1.27, 95%CI 1.17–1.39) and water leakage (OR 1.34, 95% CI 1.20–1.49) in the current home was associated with frequent common cold. Presence of cockroaches were positively (OR = 1.12, 95% CI 1.02–1.24) and presence of rats (OR = 0.86, 95% CI 0.77–0.96) negatively associated with high frequency of common cold. Daily cleaning was negatively associated with frequent common cold (OR = 0.89, 95% CI 0.81–0.97). Similar associations for mould, WPC, cockroaches and rats were found for long duration. Ambient PM10 (OR = 1.21, 95% CI 1.21–1.35 per 10 μg/m 3 ) and temperature (OR = 1.13, 95% CI 1.06–1.35 °C) on city level were associated with high frequency of common cold. Associations between cat keeping and high frequency of common cold were found only in southern China. Associations with cockroaches were stronger in northern China. Associations with dampness and mould were the same in the north and south. Conclusions: Indoor mould, water damage, windowpane condensation, cockroaches and keeping cats or dogs as pets can be risk factors for common cold while daily cleaning can be protective factor. PM10 and a warmer climate zone can be other risk factors for common cold. Highlights: Early life exposure to mould and dampness can be a risk factor for common cold. Associations for mould and dampness are similar in northern and southern China. Exposure to cats as pets can be a risk factor for common cold in southern China. Cockroaches can be a risk factor for common cold, especially in northern China. Daily cleaning of the home can be protective for common cold.